The radial modes of stars with suppressed dipole modes - Coppée, Quentin; Müller, Jonas; Bazot, Michaël; Hekker, Saskia (Astronomy and astrophysics, 2024)
Context. The Kepler space mission provided high-quality light curves for more than 16 000 red giants. The global stellar oscillations extracted from these light curves carry information about the interior of the stars. Several hundred red giants were found to have low amplitudes in their dipole modes (i.e. they are suppressed dipole-mode stars). A number of hypotheses (involving e.g. a magnetic field, binarity, or resonant mode coupling) have been proposed to explain the suppression of the modes, yet none has been confirmed. Aims. We aim to gain insight into the mechanism at play in suppressed dipole-mode stars by investigating the mode properties (linewidths, heights, and amplitudes) of the radial oscillation modes of red giants with suppressed dipole modes. Methods. We selected from the literature suppressed dipole-mode stars and compared the radial-mode properties of these stars to the radial-mode properties of stars in two control samples of stars with typical (i.e. non-suppressed) dipole modes. Results. We find that the radial-mode properties of the suppressed dipole-mode stars are consistent with the ones in our control samples, and hence not affected by the suppression mechanism. Conclusions. From this we conclude that (1) the balance between the excitation and damping in radial modes is unaffected by the suppression, and by extrapolation the excitation of the non-radial modes is not affected either; and (2) the damping of the radial modes induced by the suppression mechanism is significantly less than the damping from turbulent convective motion, suggesting that the additional damping originates from the more central non-convective regions of the star, to which the radial modes are least sensitive.
Gesehen am 21.05.2025